ANALYSIS OF THE DEVELOPMENT OF THE STARGATE ASTRA INDUSTRIAL ESTATE AS A NATIONAL STRATEGIC PROJECT IN IMPROVING COMMUNITY WELFARE - Yunus, Mochamad; Roestamy, Martin (DE'RECHTSSTAAT, 2024)
The development of the Stargate Astra Industrial Estate (KISA) in Southeast Sulawesi has garnered significant attention as part of Indonesia's government initiative to strengthen regional economy through a national strategic project. This study aims to critically analyze the implementation of KISA while considering state sovereignty in the context of natural resource management policies and regional development. The research employs a mixed-methods approach combining qualitative and quantitative analyses to explore the economic, social, and environmental impacts, as well as the implications for community rights in KISA development. Literature review emphasizes the need for balance between economic development and environmental conservation, as well as the importance of social sustainability in industrial area development processes. The analysis findings indicate that KISA development holds substantial potential to enhance local economic growth through job creation and infrastructure improvements. However, the project implementation also presents challenges related to sustainable environmental management and inclusive social integration. Therefore, recommendations include rigorous law enforcement, active community participation in decision-making, and effective risk mitigation strategies. This study aims to provide deep insights to policymakers, developers, and communities on the importance of considering state sovereignty in every step of implementing national strategic projects like KISA. Thus, ensuring sustainable economic growth without compromising environmental sustainability and local community welfare in Southeast Sulawesi.